HEGEMONI BUDAYA POP: BUDAYA BALI TERKOMODIFIKASI - I Putu Yogantara; I Nyoman Rediasa; I Wayan Sudiarta (Universitas Pendidikan Ganesha, 2026)
This research explores the phenomenon of popular culture hegemony that triggers a systematic commodification process of Balinese culture in the postmodern era. Bali, renowned for the nobility of its local wisdom, currently faces major challenges in the form of cultural clashes due to the dominance of global influences that prioritize visual-commercial aspects over fundamental values. This hegemony causes Balinese culture to be frequently repackaged into commodities that are marketable and